Lateral left ventricular lead position is superior to posterior position in long-term outcome of patients underwent cardiac resynchronization therapy. (25th November 2020) - Behon, A; Schwertner, W.R; Merkel, E.D; Kovacs, A; Lakatos, B.K; Zima, E; Geller, L; Kutyifa, V; Kosztin, A; Merkely, B
Abstract: Background: Preferring side branch of coronary sinus during cardiac resynchronization therapy (CRT) implantation is empirical due to the limited data on the association of left ventricular (LV) lead position and long-term clinical outcome. Purpose: We evaluated the long-term all-cause mortality by LV lead non-apical positions and further characterized them by interlead electrical delay (IED). Methods: In our retrospective database 2087 patients were registered between 2000 and 2018. Those with non-apical LV lead locations were classified into anterior (n=108), posterior (n=643), and lateral (n=1336) groups. All-cause mortality was assessed by Kaplan-Meier and Cox analyses. Echocardiographic response was measured 6 months after CRT implantation. Results: During the median follow-up time of 3.7 years, 1150 (55.1%) patients died, 710 (53.1%) with lateral, 78 (72.2%) with anterior and 362 (56.3%) with posterior positions. Patients with lateral position had significantly better outcome in all-cause mortality compared to others (HR 0.80; 95% CI: 0.71–0.90; p<0.0001), which was also confirmed by multivariate analysis after adjusting for relevant clinical covariates (HR 0.81; 95% CI: 0.72–0.91; p<0.0001). When echocardiographic response was evaluated in the lateral group, patients with an IED longer than 110 ms (ROC AUC 0.63; 95% CI: 0.53–0.73; p=0.012) showed 2.1 times higher odds of improvement in echocardiographic response 6 months after the implantation. Conclusions: In this study we proved that after CRT implantation only the lateral LV lead location was associated with long-term mortality benefit. Moreover, patients with this position showed the greatest echocardiographic response over 110 ms IED. Funding Acknowledgement: Type of funding source: None